Empowerment of female fishermen in Tanggul Jaya Village, Serang Banten in making organic bar soap based on sea salt and ecoenzyme - Nuryadin, Devi Faustine Elvina; Hasanah, Afifah Nurazizatul; Rosad, Rosad; Mainaki, Abdul Muid; Ramadhan, Gilang (Universitas Muhammadiyah Mataram, 2025)
Tanggul Indah Village is a village located Banten Village, Kasemen District, which is not far from the main city of Serang. This village is a coastal area with the majority of its people working as fishermen. The initial issue arose due to the use of cleaning agents such as sodium lauryl sulfate (SLS) soap which can have a negative impact on the environment. In addition, another problem is the large amount of unprocessed organic waste in the village environment. So that a community service program was carried out which aims to empower groups of women fishermen in Tanggul Indah Village through training in making organic soap based on sea salt and ecoenzyme with specific objectives to be achieved including a) management of household waste that can be used as ecoenzyme as a basic ingredient in making organic soap; b) training in making organic bar soap. The implementation method is carried out through stages, namely a) management of organic waste into ecoenzyme products; b) utilization of sea salt as a complementary ingredient in making environmentally friendly organic soap; c) empowerment and training of women fishermen in making organic bar soap. This training has gone well and received a positive response from the service participants. The active participation of each fisherwoman in every stage of the activity reflects the high enthusiasm and concern for environmental issues.